Pseudosperma quercinum sp. nov. (Inocybaceae) from the Himalayan forests of Pakistan - Naseer, Arooj; Jabeen, Sana; Ashfaq, Ammara; Akbar, Mahrukh; Hussain, Syed Iftikhar; Khalid, Abdul Nasir (Phytotaxa, 2023)
A new species, Pseudosperma quercinum, is described and illustrated from Pakistan. The species is characterized by a campanulate to conico-convex pileus, with dark brown umbo and yellow-brown fibrillose streaks on a creamy white context, creamy white to light silvery-brown lamellae, a cylindrical stipe with a fibrillose, furfuraceous, or almost flocculose stipe apex, ellipsoid to phaseoliform basidiospores, and clavate to cylindrical cheilocystidia. Molecular phylogenetic analysis inferred from the nuclear rDNA internal transcribed spacer region (ITS) and larger subunit region (LSU) confirms this species as new. In addition, we present a key and a table of comparisons to other species of this genus from Pakistan.